Developing a site-conditions map for seismic hazard Assessment in Portugal - Narciso, J. (2012)
The evaluation of site effects on a broad scale is a critical issue for seismic hazard and risk assessment, land use planning and emergency planning. As characterization of site conditions based on the shear-wave velocity has become increasingly important, several methods have been proposed in the literature to estimate its average over the first thirty meters (Vs30) from more extensively available data. These methods include correlations with geologic-geographic defined units and topographic slope. In this paper we present the first steps towards the development of a site–conditions map for Portugal, based on a regional database of shear-wave velocity data, together with geological, geographic, and lithological information. We computed Vs30 for each database site and classified it according to the corresponding geological-lithological information using maps at the smallest scale available (usually 1:50000). We evaluated the consistency of Vs30 values within generalized-geological classes, and assessed the performance of expedient methodologies proposed in the literature.